The transformation of Georgia’s tourism sector: Economic impact and strategic challenge - Suryasa, I Wayan; Zubitashvil, Tamar (International research journal of management, IT and social sciences, 2026)
This article examines the evolution of Georgia as a leading tourism destination in the Caucasus region. It analyzes the transition from a post-Soviet recreational model to a diversified international hub, highlighting the economic contributions, the role of state policy, and the emerging challenges of sustainability and over-tourism.